Pembaharuan Sistem Pendidikan Islam di Indonesia (Menggagas Format Pendidikan Islam Ideal di Tengah Arus Perubahan) - Ali Murtadlo (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract : This paper reveals some poor elements in the Indonesian education. There are several structures in education that need to be update. If this condition is left just like that, then education will not lead to the transformation of the intellect which is expected to advance the nation. Dhicotomy in education, and lack of ability of teachers, are elements that need to observed. Moreover, that ideal Islamic educational system improvement needs to be done, namely with integralistic education, humanistic, pragmatic, and rooted in a strong culture. The system needs to be refreshed to get composition of the ideal to transform the concept and implementation knowledge. However, the need to also understand the performance of the basic philosophical framework of Islamic teachings for a change with a definite direction. Therefore, education can be relevant to the needs of society in turmoil facing science and sophisticated technology. Keywords: Education, System, Islam, Indonesia, Change, and Society.